The Day After, Batu Agriculture Creative Hub Agcrea Adaptive Façade Concept - Khoiriyah, Siti; Kurniawaty, Prima; Mutiara, Elok (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 2 No 1 (2020): The 2nd International Conference on Engineering, Technology, and Social SciencesDO - 10.18860/iconetos.v2i1.1260, 2021)
The Day after means metaphorical meaning for hope, better architecture design that promotes a new design mindset. The Covid-19 crisis challenged and made us restart the perspective in architectural planning and design towards mitigating epidemic disasters. Design of Batu Agriculture Creative Hub (BACH), a creative and collaborative space for agriculture Start-Up, has considered adaptation strategies for these conditions. Inspired by the smart building strategy, especially the smart envelope for building performance toward resiliency. The smart envelope concept for BACH named agcrea (agriculture + creative), an adaptive facade design, transforms a visual representation of the identity of the local character of the Batu city logo. Kinetic moving panels respond to climate dynamics, it open and close follow the sun and wind conditions. Tested with Ecotect, the pattern of movement of the façade panels makes adjustments to the balance of natural light and ventilation to support health and comfort and energy use efficiency in buildings.